Study Of Creepage Distance Of The Contaminated Insulator In Correlation With Salt Deposit Density - Salam, Md. Abdus; Ahmad, Hussein; Ahmad, Ahmad S.; Fuad, Syed Ahmad; Paul, K. C.; Tamsir, T.; Buntat, Z.; Piah, M. A. M. (2000)
For design purposes, the specific knowledge about the creepage distance of the insulator for the contaminated environment is important. This can be done easily if the mathematical relationship between the creepage distance and Salt Deposit Density (SDD) is known. In this paper, a relationship between the creepage distance of the insulator and SDD has been proposed using the Dimensional Analysis technique. The results calculated from the proposed expression are compared with other results and found to be in close agreement